1136. Trends in Speaker Representation at the Infectious Diseases Society of America (IDSA) IDWeek Conference, 2013-2019. (31st December 2020) - Marcelin, Jasmine R; Khazanchi, Rohan; Lyden, Elizabeth; Cawcutt, Kelly; Kullar, Ravina; Kullar, Ravina; Rajapakse, Nipunie S; Ha, David R; Ristagno, Elizabeth H
Abstract: Background: Over the last decade, there have been sustained efforts to diversify the healthcare workforce. In 2016, the IDWeek Program Committee was charged to ensure gender equity in speaker sessions. Whether this intervention also resulted in more opportunities for underrepresented speakers has not been determined. Methods: This project was supported by IDSA, who provided demographic information on IDWeek speakers (excluding poster sessions) from 2013-2019. Data were summarized using descriptive statistics, and chi-square analysis evaluated changes over time. Each speaker slot was considered an independent event. Data was combined for 2013-2016 (≤2016) and 2017-2019 (>2016). IDSA membership demographics were available from 2014 for gender, race/ethnicity, from 2016 for age, and from 2018 for professional degree. Results: A total of 3640 speaker slots were filled by 2504 individuals from 2013-2019. A larger proportion of speaker slots were filled by women >2016 (51%) vs ≤ 2016 (43%), with a linear increase from 38.6% in 2013 to 52.1% in 2019 (p< 0.001). Averaged across 2013-2019, IDSA membership was 67.5% White, 20.6% Asian, 7.7% Latinx, 3.9% Black, and 0.4% Other. IDWeek Speakers during that timeframe were 77.7% White, 13.9% Asian, 4.7% Latinx, 2.7% Black, and 1.0% Other; a larger proportion of slots were filled by Asian speakers >2016 (16.3%) vs ≤ 2016 (12.8%) (p=0.005). The proportion of pharmacist speakers increased over time; 5.1% of speakers in 2019 reflected IDSA pharmacist membership (5.4%). The proportion of individuals invited to speak more than once differed by age (19% in < 40yo, 28% 40-49yo, 32% 50-59yo, and 22% >60yo; p< 0.001), and professional degree (28% physicians, 18% pharmacists, 9% other doctorates, and 7% non-doctorate speakers; p< 0.001). Figure 1: Trends in Gender Distribution of IDWeek Speakers and IDSA Members, 2013-2019 Figure 2: Trends in Race/Ethnicity Distribution of IDWeek Speakers and IDSA Members, 2013-2019 Conclusion: Intentional consideration of gender equity by the Program Committee significantly improved equitable gender representation of invited speakers at IDWeek. This effort has not resulted in increased diversity of invited speakers from groups underrepresented in IDSA membership. To ensure that invited speakers represent the membership of IDSA/IDWeek partner organizations and more importantly, the communities we serve, we call for continued application of the principles of Inclusion, Diversity, Access, and Equity at IDWeek. Disclosures: All Authors : No reported disclosures